2019
DOI: 10.1038/s41598-019-42804-8
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Effects on Natural Mammalian Populations: Correlation Between Telomere Length and Coal Exposure

Abstract: The Candiota coal mine in Rio Grande do Sul (RS) is one of the largest in Brazil. Coal is a fossil fuel that causes environmental impacts from its extraction to combustion due to the release of different agents, such as polycyclic aromatic hydrocarbons (PAH) and heavy metals. C tenomys torquatus are herbivorous and subterranean rodents that dig tunnels with their paws and teeth and can be exposed to coal through contaminated food. Exposure to pollutants can cause DNA damage and affect di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…For example, changes in telomere length have been observed in relation to variation in abiotic or biotic conditions, such as the hydric regime (Dupoué et al 2020), temperature (Simide et al 2016, Nowack et al 2019, Burraco et al 2020a), predation risk (Kärkkäinen et al 2019), nutrient quality (Noguera et al 2015) or exposure to parasites (Asghar et al 2015). Anthropogenic disturbances such as the ones linked to urbanisation (Ibáñez‐Álamo et al 2018) or pollution (Matzenbacher et al 2019) have also been associated with shorter telomere lengths. Theoretically, under stressful conditions, faster telomere shortening could be the consequence of the prioritisation of processes ensuring immediate survival rather than telomere maintenance (Casagrande and Hau 2019), a pattern that may be exacerbated at early life stages (Monaghan and Ozanne 2018, Young et al 2018).…”
Section: Environmental Drivers Of Telomere Length Variationmentioning
confidence: 99%
“…For example, changes in telomere length have been observed in relation to variation in abiotic or biotic conditions, such as the hydric regime (Dupoué et al 2020), temperature (Simide et al 2016, Nowack et al 2019, Burraco et al 2020a), predation risk (Kärkkäinen et al 2019), nutrient quality (Noguera et al 2015) or exposure to parasites (Asghar et al 2015). Anthropogenic disturbances such as the ones linked to urbanisation (Ibáñez‐Álamo et al 2018) or pollution (Matzenbacher et al 2019) have also been associated with shorter telomere lengths. Theoretically, under stressful conditions, faster telomere shortening could be the consequence of the prioritisation of processes ensuring immediate survival rather than telomere maintenance (Casagrande and Hau 2019), a pattern that may be exacerbated at early life stages (Monaghan and Ozanne 2018, Young et al 2018).…”
Section: Environmental Drivers Of Telomere Length Variationmentioning
confidence: 99%
“…Telomeres protect the ends of chromosomes to stabilize the nuclear genome with high delity during youth but usually decreasing during aging and with the in uence of environmental agents and diseases 51,52 . The relationship between TL shortening and aging was not observed in this study, although juvenile organisms presented larger telomeres than subadults and adults (shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Telomere length (TL) was quanti ed from the total C. minutus genomic DNA by using a real-time quantitative Polymerase Chain Reaction (qPCR) method following the protocol according to Callicott and Womack 64 , with minor modi cations by Matzenbacher et al 52 . The forward and reverse primer sequences for the telomeric region gene were 5' CGG TTT GTT TGG GTT TGG GTT TGG GTT TGG TTT GGG TT 3' and 5' GGC TTG CCT TAC CCT TAC CCT TAC CCT TAC CCT TAC CCT 3', respectively.…”
Section: Telomere Length Analysis By Qpcrmentioning
confidence: 99%
“…Significant positive correlations in tissue TL have been reported in other vertebrates including macaques ( Macaca fascicularis ; Gardner et al., 2007), dogs ( Canis lupus familaris ; Benetos et al., 2011), zebra finches ( Taeniopygia guttata ; Reichert et al., 2013) and painted dragon lizards ( Ctenophorus pictus ; Rollings et al., 2019). Studies in nonmodel mammalian species found no significant differences between liver, kidney, muscle and skin rTL in collared tuco‐tucos ( Ctenomys torquatus ; Matzenbacher et al., 2019) while significant correlations in rTL were found across liver, brain, ovary and heart in the bank vole ( Myodes glareolus ; Kesäniemi et al., 2019). Furthermore, a study on brown trout ( Salmo trutta ) found fin rTL to correlate significantly with other tissue rTLs, allowing a noninvasive measurement of telomeres (Debes et al., 2016).…”
Section: Introductionmentioning
confidence: 99%